Alteration of the gut microbiome and immune factors of grass carp infected with Aeromonas veronii and screening of an antagonistic bacterial strain (Streptomyces flavotricini). (June 2020) - Huang, Haiyan; Zhou, Pengji; Chen, Pei; Xia, Liqiu; Hu, Shengbiao; Yi, Ganfeng; Lu, Jiaoyang; Yang, Shuqing; Xie, Junyan; Peng, Jinli; Ding, Xuezhi
Abstract: Aeromonas veronii is a widely distributed novel pathogen that can affect humans and animals, it can cause sepsis in fish with high mortality and serious economic losses to aquaculture. In the study, the gut microbiome of the infected and uninfected grass carp with Aeromonas veronii were analyzed probiotics and pathogenic bacteria by the Miseq high-throughput sequencing, the results showed that the infected fish were significantly higher in Proteobacteria, Firmicutes, Fusobacteria, and the immune factors in liver and kidney were up-regulated by qRT-PCR. In order to effectively inhibit the pathogen, we screened an actinomycete strain and had good antibacterial effect on Aeromonas veronii . The new antagonistic bacteria was named as Streptomyces flavotricini X101, the whole genome sequencing revealed that the metabolic process was most active. After grass carp was inoculated with the minimum inhibitory concentration of 900 μg/mL of the strain's fermentation supernatant, then Aeromonas veronii was injected, we found that the pathological symptoms such as body surface, anus and abdominal congestion were alleviated by H&E staining. Cellular experiments showed that it wasn't toxic to liver cells of grass carp. Overall, this is the first study of changes in intestinal flora, phenotype, and immune factors in grass crap infected with Aeromonas veronii, it had important theoretical significance and application value for immunization and prevention. Highlights: Immune factors are up-regulated after infection with Aeromonas veronii. The intestinal flora of grass carp has obvious changes in test group. It's the first report about Streptomyces flavotricini as fish antagonistic bacteria.